Monitoreo y control espacial de la sigatoka negra (mycosphaerella fijiensis m), en el cultivo del banano - Carrion Ramon, Jefferson Javier (Machala : Universidad Técnica de Machala, 2020)
Banana is one of the main export items of Ecuador, the farms where bananas are grown fight every day against the disease that strongly attacks this fruit, the Black Sigatoka is caused by the fungus Mycosphaerella Fijiensis Morelet constituting one of the costs higher in banana production due to the fact that it directly attacks the banana leaves that are the photosynthesis engine to produce starches and thus achieve a fruit of excellent weight and quality, thus causing approximately up to 50% loss in yield . The disease will spread to great distances if the necessary precautions are not taken. The applications of fungicides cause great environmental impact causing contamination and raising production costs, few are the researchers or producers who focus their vision to control this disease from an ecological point of view, reducing the chemical load of conventional fungicides using more alternatives. environmentally friendly and more effective tools such as the use of spatial maps through GIS for the determination of infection foci that are areas of great impact in a banana plantation that makes it a great source of inoculum in the plantations. established to determine the focus of infection of the fungus (Mycosphaerella fijiensis Morelet) by means of the IDW spatial method and its incidence in the plantation in the 4th and 5th leaf stages and the number of total leaves in plants of 0 weeks and at harvest. Once the infection foci on the farms were determined, the treatments were T1 = control with spatial analysis and biological products and T2 = control with spatial analysis and synthetic products and the Control which is a farm that does not use spatial analysis and fumigates every 8 to 10 days with agricultural oil in a common way, the use of GIS through spatial analyzes maintained a direct effect on the presence of stages where it was considerably reduced with a high regression of R2 = 0.97 in T1 while T2 obtained an R2 = 0.96 while that the control maintained a reduction with an R2 = 0.66, at 13 weeks the average effect of the stages in the 4th leaf was for T1 = 1.74 a, T2 = 2.29 b and T3 = 2 ab, in the 5th leaf a high regression of R2 = 0.98 in T1 while T2 obtained an R2 = 0.91 while the control maintained a reduction with R2 = 0.64 in the same way at 13 weeks the average effect of the stages in 5th leaf were for T1 = 1.94 a , T2 = 2.37 b and T3 = 2.07 where the T1 is equal to the Control, it is concluded that the use of GIS identifying the foci of infection of black sigatoka allowed to make a local application of the areas with the greatest source of inoculum obtaining results as a reduction of the evolutionary stages in early infection where the presence of stages was significantly reduced in 90 days and at the same time there was a significant increase in the number of leaves at harvest.
El banano es uno de los principales rubros de exportación del Ecuador, las haciendas donde se cultiva banano luchan día a día contra la enfermedad que ataca fuertemente a esta fruta, la Sigatoka Negra es causada por el hongo Mycosphaerella Fijiensis Morelet constituyendo en uno de los costos más elevados en la producción bananera debido a que ataca directamente a las hojas de banano que son el motor de fotosíntesis para producir almidones y así lograr a tener una fruta de excelente peso y calidad, causando así aproximadamente hasta el 50% de perdida en el rendimiento. La enfermedad se extienda a grandes distancias si no se tiene las precauciones necesaria. La aplicaciones de fungicidas causa gran impacto ambiental provocando contaminación y elevación de los costos de producción, pocos son los investigadores o productores que centran su visión al control de esta enfermedad desde un punto de vista ecológico reduciendo la carga química de los fungicidas convencionales utilizando alternativas más amigables con el ambiente y herramientas más eficaces como el uso de los mapas espaciales mediante los SIG para la determinación de los focos de infección que son zonas de gran impacto en una bananera que la convierte en un gran fuente de inoculo en las plantaciones por ello se estableció determinar el foco de infección del hongo (Mycosphaerella fijiensis Morelet) mediante el método espacial IDW y su incidencia en la plantación en los estadíos de 4ta y 5 ta hoja y el numero de hojas totales en plantas de 0 semanas y a la cosecha. Una vez determinado los focos de infección en las fincas los tratamientos fueron T1= control con análisis espacial y productos biológicos y T2= control con análisis espacial y productos sintéticos y el Testigo que es una finca que no usa análisis espacial y fumiga cada 8 a 10 días con aceite agrícola de manera común, el uso de los SIG mediante los análisis espaciales mantuvo un efecto directo sobre la presencia de estadíos donde se redujo considerablemente con una alta regresión de R2= 0.97 en el T1 mientras el T2 obtuvo un R2=0.96 mientras que el testigo mantuvo una reducción con un R2= 0.66, a las 13 semanas el efecto promedio de los estadios en 4ta hoja fueron para T1=1.74 a , T2= 2.29 b y T3= 2 ab, en la 5ta hoja se puede observar una alta regresión de R2= 0.98 en el T1 mientras el T2 obtuvo un R2=0.91 mientras que el testigo mantuvo una reducción con un R2= 0.64 de igual manera a las 13 semanas el efecto promedio de los estadios en 5ta hoja fueron para T1=1.94 a , T2= 2.37 b y T3= 2.07 a donde el T1 es igual al Testigo, se concluye que el uso de los SIG identificando los focos de infección de sigatoka negra permitio hacer una aplicación localiza de las zonas de mayor fuente de inoculo obteniendo resultados como reducción de los estados evolutivos en infección temprana donde la presencia de estadios se redujo notablemente en 90 días y a su vez que existio un incremento significativo del número de hojas a la cosecha.
Keywords: SIGATOKA; NEGRA; HOJAS; BANANO